Defending the Profession: U.S. Journalists' Role Understanding in the Era of Fake News. (7th February 2023) - Jahng, Mi Rosie; Eckert, Stine; Metzger-Riftkin, Jade
ABSTRACT: Using theories of journalists' role perception, we analyzed how U.S. mainstream journalists defined "fake news, " and signaled to audiences the difference between their own news stories and "fake news" to defend their profession and a particular narrative of their profession as crucial to democracy. Results from interviews yield a split definition of "fake news:" journalists' own understanding of the term and how journalists see their audiences apply the term. Participants defended their news reporting process by highlighting traditional best practices and new tools to verify information. In order to justify their profession's purpose and legitimacy in democracy, journalists emphasized strategies of highlighting institutional history, transparency, and community engagement.